2002
DOI: 10.1007/s00024-002-8680-4
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Source, Propagation and Site Effects from S Waves¶of Local Earthquakes in Bursa Region, Northwestern Turkey

Abstract: Ð We have used micro-earthquake recordings (M 1.8±4.1) of local events in the distance range of 5±60 km in order to quantify the attenuation and site eects in the vicinity of the Bursa city, Marmara region, Turkey. The data set consists of 120 three-component recorded accelograms from 69 earthquakes, recorded at six stations. Each station is deployed on dierent geologic units, such as massive limestone, slope deposit and Quaternary young sediments, in the framework of the Marmara Poly-Project.In this study a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 6 publications
(8 reference statements)
0
4
1
Order By: Relevance
“…Among the earlier studies on the neighboring areas of Turkey, Eck [1988] at 25 s were calculated by Rahimi and Hamzehloo [2008]; the average frequency relation for Central Iran was determined as Q c =(79±2)f (1.07±0.08) by Rahimi et al [2010]; a regional Q c =126f 1.05 relation was approximated by Meirova and Pinsky [2004] based on S wave coda decay rate for Israel. The discrepancies between the present results and those ones obtained in previous studies of Marmara Region reported in "Introduction" section and in Table 6 might be due to the differences in the considered window lengths and kind of quality factor vary from one author to another [Barış et al, 1992;Horasan et al, 1998;Kaşlılar-Özcan, 1999;Akyol et al, 2002;Horasan and Boztepe-Güney, 2004;Sertcelik and Guleroglu, 2017]. Generally, most of the studies demonstrate <200 of Q values and this suggest an active tectonic settings.…”
Section: Resultscontrasting
confidence: 82%
“…Among the earlier studies on the neighboring areas of Turkey, Eck [1988] at 25 s were calculated by Rahimi and Hamzehloo [2008]; the average frequency relation for Central Iran was determined as Q c =(79±2)f (1.07±0.08) by Rahimi et al [2010]; a regional Q c =126f 1.05 relation was approximated by Meirova and Pinsky [2004] based on S wave coda decay rate for Israel. The discrepancies between the present results and those ones obtained in previous studies of Marmara Region reported in "Introduction" section and in Table 6 might be due to the differences in the considered window lengths and kind of quality factor vary from one author to another [Barış et al, 1992;Horasan et al, 1998;Kaşlılar-Özcan, 1999;Akyol et al, 2002;Horasan and Boztepe-Güney, 2004;Sertcelik and Guleroglu, 2017]. Generally, most of the studies demonstrate <200 of Q values and this suggest an active tectonic settings.…”
Section: Resultscontrasting
confidence: 82%
“…There are many studies that focus on modeling and mitigation, especially earthquake risk of the city of Bursa (Öncü 2021;Taş 2003). A number of studies deal with local site effect problems, since the city of Bursa is located in a deep alluvial basin (Akyol et al, 2002a;2002b;Topal et al, 2003 Subaşı et al 2019). The effect of soil ampli cation in Bursa was also observed in far-eld earthquakes (Ansal et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Boreholes undertaken by the General Directorate of State Hydraulic Works of Turkey (DSI) and private companies indicate that the thickness of unconsolidated materials underlying the basin ranges from 100 to 300 m (ULUSAY et al, 2000). There are many basins in Turkey which have similar characteristics with Cukurova, such as the Bursa, Dinar and Erzincan basins (AKYOL et al, 2002;YALCINKAYA and ALPTEKIN, 2003), and most of these basins are located in the first degree earthquake regions according to the Seismic Zoning Map of Turkey. Knowledge of the site response in these basins is important to mitigate the seismic risk.…”
Section: Introductionmentioning
confidence: 99%